2019
DOI: 10.5489/cuaj.6154
|View full text |Cite
|
Sign up to set email alerts
|

A fountain of knowledge? The quality of online resources for testicular cancer patients

Abstract: Introduction: Testicular cancer is the most common solid malignancy diagnosed in young men aged 15–29. This population is also the age group that searches most actively for health information online. This study systematically evaluates the quality of websites available to patients with testicular cancer. Methods: The term “testicular cancer” was inputted into the search engines Google, Dogpile, and Yippy. The top 100 websites intended for patient education were compiled. A validated structural rating too… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 27 publications
1
7
0
Order By: Relevance
“…This is surprising given recent research which found that the average readability level of testicular cancer resources was challenging at a Flesh Kincaid grade level of 11. 24 However this may be explained again by our younger patient demographic, as it has been shown that young adults are the most proficient in technology rich environments and that health literacy skills decline with age. 30,31 Despite the benefits of the internet, about half of the respondents reported that online information did not influence their consultations with health care providers or treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is surprising given recent research which found that the average readability level of testicular cancer resources was challenging at a Flesh Kincaid grade level of 11. 24 However this may be explained again by our younger patient demographic, as it has been shown that young adults are the most proficient in technology rich environments and that health literacy skills decline with age. 30,31 Despite the benefits of the internet, about half of the respondents reported that online information did not influence their consultations with health care providers or treatment decisions.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have found that metrics commonly used by patients to determine reliability, such as authorship, currency and citations are lacking in many online testicular cancer resources. [24][25][26] This highlights a potential role for health care providers to discuss with patients about how/where they obtain their online information and help them interpret what they find. 27 Although the majority of participants used the internet to search for testicular cancer information, less than half spoke with their provider regarding their findings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is in line with findings for other cancer patient online material. 24,25 Comparison of physician and publicly provided websites revealed important differences. Publicly provided content was more accurate according to the quality of information given.…”
Section: Discussionmentioning
confidence: 99%
“…25,26 A recent publication by Yeo et al suggested that, with the increase in patients acquiring information about testicular cancer from sources that are not validated or credible, direct patient education has become even more important. 28 Directing patients towards validated testicular cancer education programs is beneficial for patient-physician communication, as well as overall patient understanding. The testicular cancer model described in this study can serve as an adjunct for patient education and facilitate discussion regarding the benefits of screening and the risk of testicular malignancy.…”
Section: Cuaj -Original Researchmentioning
confidence: 99%